PERUBAHAN KEBIJAKAN PERIZINAN INVESTASI BESERTA PELAKSANAANNYA DI DIY - Eni Kusdarini (LPPM UNY, 2003)
Abstract This discus shows the change of the policy of investment license specially uses the Foreign direct Investment and Domestic Investment (PMA/PMDN) facilities in Indonesia for region autonomy program. The purpose of this discussion is to descript that change and to know the procedure and also the application in DIY. The teorities advantages of the discussion are to help increasing the theory, which is in economics rules, related the policy. While the real advantages is to give input for arrange of investment policy above related the obstruction of the application. Then investor will get the description how to take investment license has been done in Habibie era. The change is the give of investment license is taken by Badan Penanaman Modal (BPM), but now that is taken by BPMD/BAPEKOINDA province if the Domestic Investment (PMDN) more than ten billion rupiahs and there is no foreign elemens. Also BPMD have authority in finishing investment. Keywords: the policy of license investment, foreign direct investment, domestic investment.